2009
DOI: 10.1158/1535-7163.mct-08-0914
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostuslactone disrupts signal transducers and activators of transcription 3 through up-regulation of suppressor of cytokine signaling in breast cancer cells

Abstract: This study investigates the anticancer effect of dehydrocostuslactone (DHE), a plant-derived sesquiterpene lactone, on human breast cancer cells. DHE inhibits cell proliferation by inducing cells to undergo cell cycle arrest and apoptosis. DHE suppresses the expression of cyclin D, cyclin A, cyclin-dependent kinase 2, and cdc25A and increases the amount of p53 and p21, resulting in G 0 /G 1 -S phase arrest in MCF-7 cells. In contrast, DHE caused S-G 2 /M arrest by increasing p21 expression and chk1 activation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 43 publications
(85 reference statements)
6
46
1
Order By: Relevance
“…under the same conditions, exposure to dehydrocostuslactone resulted in significant apoptosis in all the cell lines examined. This is consistent with reports that dehydrocostuslactone is an effective anticancer agent capable of inducing apoptosis (14)(15)(16)(17). apoptosis is an important series of events that lead to programmed cell death, and is essential for development and tissue homeostasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…under the same conditions, exposure to dehydrocostuslactone resulted in significant apoptosis in all the cell lines examined. This is consistent with reports that dehydrocostuslactone is an effective anticancer agent capable of inducing apoptosis (14)(15)(16)(17). apoptosis is an important series of events that lead to programmed cell death, and is essential for development and tissue homeostasis.…”
Section: Discussionsupporting
confidence: 92%
“…a similar pattern was observed for breast cancer cells, although the effect was weaker than that observed in the ovarian cancer cells (~1.3 to 2.3-fold increase compared to the respective controls). dehydrocostuslactone has been shown to induce cell cycle arrest at the G2/M phase in several cancer cell lines in vitro (14,15). This is consistent with our results, which indicated that exposure to dehydrocostuslactone induces significant cell cycle arrest.…”
Section: Discussionsupporting
confidence: 92%
“…Costunolide and dehydrocostus lactone, major sesquiterpene lactones derived from 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 S. lappa, are reported to induce cell death in some cancer cells (9e11). Dehydrocostus lactone has been shown to induce apoptosis in lung cancer (12), breast cancer (13), hepatocellular carcinoma (14), prostate cancer (15) and leukemia (16). Costunolide has also been shown to induce apoptosis in bladder cancer (17), breast cancer (18), ovarian cancer (19), and leukemia (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Saussurea costus is considered to be one of the antioxidant-rich medicinal plants. Many authors have reported that the roots of this plant possess various biological activities, including cortisol lowering effect [38], anti-infammatory [39,40], anticancer [41,42], antiviral [23], antimicrobial [43,44], antifungal [15], antioxidant [45,46], antidiabetic [47], antiulcer [20] and hepatoprotective effects [38]. Liv-52 is widely used in treatment of liver diseases of varying origins.…”
Section: Discussionmentioning
confidence: 99%